Pengaruh Pengetahuan, Keterampilan dan Kemampuan Karyawan terhadap Kinerja Karyawan (Studi pada Industri Kerajinan Kulit di Manding, Bantul, Yogyakarta) - Suhartini, Yati (Universitas PGRI Yogyakarta, 2015)
The research was carried out to find the influence of knowledge, skill and ability of leather industry in Manding-Bantul, Yogyakarta. The population of this research were all employees at leather industry in Manding Bantul, Yogyakarta and the sample were 60 respondents. The data was derived from a survey and collected by applying questionnaires and analyzed by using multiple linear regressions. This research indicated that factors of knowledge, skill dan ability, all together showed a significant influence on the worker performance. These were indicated by the value of F amounting to 46,328 with the significance level of 0,000, where as R square counting to 0,713. The regression coefficient and the significant level of each factor of knowledge, skill and ability toward worker performance are 0,145 and 0,012; 0,541 and 0,000; 0,304 and 0,000; respectively.